2009
DOI: 10.1017/s1537592709090781
|View full text |Cite
|
Sign up to set email alerts
|

The Blind Man and the Elephant in the Room: Robert Lieberman and the Israel Lobby

Abstract: Robert Lieberman's critique of our work on the Israel lobby is at odds with an abundance of evidence and prior scholarship describing the powerful influence that pro-Israel groups exert on U.S. Middle East policy. In addition to mischaracterizing our arguments, Lieberman claims that our methodology and research design are flawed and that our work contradicts the scholarly literature on American politics. Neither claim is true. Contrary to what he says, we did consider alternative hypotheses, and our analysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Process-tracing analysis Usually employed in small-n research to identify "the key events, individuals, relationships and decisions that link causal conditions to outcomes" (Young, 2012, p. 671) To draw "descriptive and causal inferences from diagnostic pieces of evidence-often understood as part of a temporal sequence of events or phenomena" (Collier, 2011, p. 824) Arnold & Fleischman, 2013Caoutte, 2007;Collier, 2011;Mearsheimer & Walt, 2009;Schroeder, 2008 Attributed-influence method "To ask the members of the group under examination to rank each other according to influence, either over the individual respondent or over the group as a whole (re a particular situation)" (March, 1955, p. 445) Dür & De Bièvre, 2007Dür, 2008a;Güell, 2011;Pappi & Henning, 1999 Preference Attainment "To compare policy preferences of interest groups with the policy output in order to draw conclusions about the winners and losers of the decision-making process" (Klüver, 2009, p. 536) Baumgartner et al, 2009Mahoney, 2007Mahoney, , 2008Schneider, Finke, & Baltz, 2007a;Scott, 2013 EAR Instrument To assess influence in decision making by looking at (a)…”
Section: Applied Bymentioning
confidence: 99%
“…Process-tracing analysis Usually employed in small-n research to identify "the key events, individuals, relationships and decisions that link causal conditions to outcomes" (Young, 2012, p. 671) To draw "descriptive and causal inferences from diagnostic pieces of evidence-often understood as part of a temporal sequence of events or phenomena" (Collier, 2011, p. 824) Arnold & Fleischman, 2013Caoutte, 2007;Collier, 2011;Mearsheimer & Walt, 2009;Schroeder, 2008 Attributed-influence method "To ask the members of the group under examination to rank each other according to influence, either over the individual respondent or over the group as a whole (re a particular situation)" (March, 1955, p. 445) Dür & De Bièvre, 2007Dür, 2008a;Güell, 2011;Pappi & Henning, 1999 Preference Attainment "To compare policy preferences of interest groups with the policy output in order to draw conclusions about the winners and losers of the decision-making process" (Klüver, 2009, p. 536) Baumgartner et al, 2009Mahoney, 2007Mahoney, , 2008Schneider, Finke, & Baltz, 2007a;Scott, 2013 EAR Instrument To assess influence in decision making by looking at (a)…”
Section: Applied Bymentioning
confidence: 99%
“…Indeed, it is a widely shared belief in contemporary European publics that antisemitism has largely dissipated and generally become socially and politically irrelevant-even though such claims are difficult to substantiate and contradict social research findings. If antisemitism surfaces as a problem today, it is frequently suggested that it is instrumentalized and overused, presumably constituting an ubiquitous political charge allegedly employed by Jewish and Israeli lobbies in order to suppress dissent and fence off criticism of Israel in Europe and the United States (see, for instance, Mearsheimer & Walt 2009; for a scholarly critique of these claims, see Lieberman 2009a;2009b). In a similar vein, some scholars and political pundits have suggested that the European radical right, with its anti-Muslim vigor, has turned "pro- Israel" and "pro-Jewish" (Bunzl 2007).…”
Section: Javier Domínguez Arribas 258mentioning
confidence: 99%
“… See, for instance, the debate about the role of the “Israel lobby” in US policy toward Israel and the Middle East (Mearsheimer and Walt 2006a,b, 2009; Lieberman 2009a,b). An analysis of this debate and specific pathways of the influence of certain interests groups on US foreign policy is beyond the scope of this essay. …”
mentioning
confidence: 99%